Nasal Profile Hump Reduction Using the Let-Down Technique - Montes-Bracchini, Jose Juan (Facial Plastic Surgery, 2019)
In rhinoplasty, the nasal dorsum represents an important aspect for form and function. Surgical management should be performed accurately to avoid complications. The goal for dorsal preservation is to preserve the keystone area intact above the nasal bones and its relationship with the upper lateral cartilages. Unlike other rhinoplasty techniques, the lowering of the nasal dorsum requires dorsal modification prior to the surgery of the tip since it modifies the tip position by rotating it. Unlike the push-down technique, that places the nasal bones inside the nasal cavity, producing obstruction of the airway, the let-down technique improves the airway and releases the valve area, making it a functional-friendly technique.
Keywords: let down; push down; keystone area